Factors Associated With Patient-Centered Medical Home Teams' Use of Resources for Identifying and Approaches for Managing Patients With Complex Needs. Issue 3 (July 2022) - Stockdale, Susan E.; Rose, Danielle E.; McClean, Michael; Rosland, Ann-Marie; Chang, Evelyn T.; Zulman, Donna M.; Stewart, Gregory; Nelson, Karin M.
Abstract : Using data from a Veterans Health Administration national primary care survey, this study identified the most highly rated tools and care approaches for patients with complex needs and how preferences varied by professional role, staffing, and training. Nurses were significantly more likely to rate most tools as very important as compared with primary care providers. Having a fully staffed team was also significantly associated with a very important rating on all tools. Nurses and fully staffed teams reported a greater likeliness to use most care approaches, and those with perceived need for training reporting a lower likeliness to use.